Struggling to learn : an intimate history of school desegregation in South Carolina - Thomas, June Manning (University of South Carolina Press, 2021)
"Author June Manning Thomas offers an intimate history of her experiences in Orangeburg, South Carolina during the 1960s. Thomas was among the plaintiffs in the court case Adams v. School Dist. No. 5, Orangeburg County (1964) and as a result was part of the first group of African American students to attend racially integrated public schools in Orangeburg. Thomas discusses her experiences with a sense of emotion and intimacy that helps readers to better comprehend the complexity of this moment. An academic by training, having received a Ph.D. in urban and regional planning and holding a distinguished professorship at the University of Michigan, Thomas overlays her own memories with archival research and secondary literature. This results in a historically minded memoir that deftly weaves broad historical context with a keen sense of personal experience. Thomas again brings a unique insight that builds upon the position of her family in the struggle for desegregation. Thomas' father was H.V. Manning, who served as president of Claflin University (1956-1984). This gave Thomas a unique position from which to view events in South Carolina, and especially in Orangeburg. Even in the sections of the manuscript that are more focused on historical framing, Thomas suffuses the text with her personal experiences and insights. Chapter 2, for instance, discusses her father's role in working for greater educational access for African Americans students. Chapter 5 then talks about economic boycotts in Orangeburg as a mechanism of protest. It also offers a first-hand account of the Orangeburg Movement. The heart of the book, however, comes in chapters 7-9, where Thomas discusses her own experiences as one of the first generation of African American students in South Carolina to attend desegregated schools, first in Orangeburg and then at Furman University in Greenville. Thomas' narrative is rich and complex. It highlights the ambiguities and internal tensions of the struggle for school desegregation and this period of South Carolina's history more generally"--